Bulletin of the geological society of America - Geological Society of America ([New York, N.Y.] : The Society, 1961)
Vols. 1-44 include Proceedings of the annual meeting, 1889-1933, later published separately.
Title from cover.
Keywords: Geology -- Periodicals; Geologie